2022
DOI: 10.1080/2162402x.2022.2073050
|View full text |Cite
|
Sign up to set email alerts
|

NPM1 and DNMT3A mutations are associated with distinct blast immunophenotype in acute myeloid leukemia

Abstract: The immune system is important for elimination of residual leukemic cells during acute myeloid leukemia (AML) therapy. Anti-leukemia immune response can be inhibited by various mechanisms leading to immune evasion and disease relapse. Selected markers of immune escape were analyzed on AML cells from leukapheresis at diagnosis (N = 53). Hierarchical clustering of AML immunophenotypes yielded distinct genetic clusters. In the absence of DNMT3A mutation, NPM1 mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…However, although many mutations in DNMT3A are cataloged, few have been thoroughly investigated, with point mutations in the catalytic domain being the major players associated with AML drivers [91]. Other studies have shown that patients with DNMT3A mutation present higher levels of HLA-DR, CLIP, PD-L1, and TIM-3 and lower levels of CD34 (Figure 2) [89,92,93]. The majority of studies in Table 1 (7/10) reported the presence of CD34+ immunophenotypic markers in most patients.…”
Section: Immunophenotyping X Genetics In Amlmentioning
confidence: 99%
“…However, although many mutations in DNMT3A are cataloged, few have been thoroughly investigated, with point mutations in the catalytic domain being the major players associated with AML drivers [91]. Other studies have shown that patients with DNMT3A mutation present higher levels of HLA-DR, CLIP, PD-L1, and TIM-3 and lower levels of CD34 (Figure 2) [89,92,93]. The majority of studies in Table 1 (7/10) reported the presence of CD34+ immunophenotypic markers in most patients.…”
Section: Immunophenotyping X Genetics In Amlmentioning
confidence: 99%